Matemática inclusiva: formação de professores para o ensino de Matemática em classes hospitalares - Teixeira, Uyara Soares Cavalcanti (2018)
This research is inserted in the area of Mathematics Concentration in Basic Education and presents as theme mathematical education and school inclusion. It aims to contribute to the process of training teachers who teach mathematics in the hospital classes. Methodologically, the study starts from an exploratory, qualitative-based research with support in action research in the integral and systemic perspective. As a result, among others, the study provided a solid and concise training to the teachers of the Núcleo de Atendimento Educacional Hospitalar (NAEH), built with the support of the actors and authors involved; discussions that referred to new perspectives of formation, involving other areas of knowledge; a continuous space of dialogue, a basis for understanding the concept of continuing education. The research sought to contribute to the strengthening of the group of teachers, presented new work opportunities and expanded knowledge in the field of mathematics, an area presented as a deficit by teachers.